Guide to standards and specifications for designing Web software - Magee, Stan (Artech house, 1998)
This book deals with standards and specifications that cover topics such as: APIs, authentication, binding, bridges, CIDR, databases, DHCP, e-mail, encryption, gateway, HIPPI, HTML, HTP, IMAP, IP, JPEG, keys, LAN, Mailbox, MIBs, MIME, MPEG, network nodes, POP, privacy, RIP, routers, security, servers, SGML, TCP, TCP/IP, URL, URN, video, web languages, X400, X500, XML, and many more. It lists specifications produced by organizations such as: AES, AIIM, ANSI, DoD, IEEE, IMS, ISO, ISOC, ITU-T, Microsoft, Netscape, NIST, SMPTE, Sun, VXI, and W3C.